Determination of Radio Environmental Level in Hydrogen (HI) Band Spectrum by using Kurtosis Analysis - Zafar, S.N.A.S.; Umar, R.; Sabri, N.H.; Ibrahim, Z.A.; Kamarudin, M.K.A.; Endut, A. (Insight Society, 2017)
The Radio Frequency Interference (RFI) nowadays becomes a serious problem and crucial issue in the radio astronomy observation. The radio astronomical lines observation become worse due to the more RFI in Ultra High Frequency (UHF) and Very High Frequency (VHF) which influences the data in radio image. The aims of this paper are to investigate the radio environment level in hydrogen (HI) band (1300-1500MHz) and also in a wide band (0-9000 MHz). The observation site is at KUSZA Observatory (KO), Langkawi National Observatory (LNO) and East Coast Environmental Research Institute (ESERI). In this paper, the statistical kurtosis and waterfall method are applied on the radio environment data. The highest average of kurtosis values indicates the lowest of radio environment level at these sites. From obtained results, the highest average of kurtosis value in wide band obtained at 'LNO' which 20.33 and in the specific band was found at 'KO' with a value of 6.06. This preliminary study is important to identify the radio environment level in radio astronomical specific band such as HI band.